Exploring the Influence of Price Perception, Product Quality, and Promotion on Consumer Purchase Decisions - Haslindar Ibrahim; Hala Najwan Sabeh; Nurul Syahira Shamsuddin; Nurul Nazirah Syed Abu Bakar; Nurul Sofia Maisara Nor Hazlan; Olyviana Lu Hui Xin; Ong Shun En; Anees Jane Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
This research aims to understand how customer’s views on price, product quality and promotional offers influence their decision to buy from Mixue, a popular brand offering ice creams and drinks. Businesses that want to remain competitive must understand the factors influencing shifting consumer preferences. Quantitative research is the methodology used in this research. The survey questions via Google Forms are distributed to 101 respondents focusing on Mixue’s customers. The results reveal that favourable price perception and high product quality significantly increase the likelihood of purchase, while promotional activities also play a key role in attracting new customers. However, these results emphasize how crucial it is for Mixue to continue providing high-quality products at competitive prices and diversify its promotional strategies to enhance customer engagement and boost purchase decisions